2017
DOI: 10.7567/jjap.56.04ca02
|View full text |Cite
|
Sign up to set email alerts
|

Cu(In,Ga)(Se,S)2solar cell research in Solar Frontier: Progress and current status

Abstract: As the largest manufacturer of Cu(In,Ga)(Se,S)2 (CIGS) thin-film photovoltaic modules with more than 1 GW/year production volume, Solar Frontier K.K. has continuously improved module performance and small-area cell efficiencies in the laboratory. Because of our low-cost and environmentally-friendly process, Solar Frontier’s CIGS is a promising technology for the mass production of photovoltaic modules to fill ever-increasing demand. Recently we have achieved certified efficiencies of 22.3 and 22.0% on CdS-buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
119
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 46 publications
2
119
1
1
Order By: Relevance
“…The GGI was calculated to be 0.6 using Eqs. (1) and (2). We confirmed that the GGI agreed well with the chemical element compositions by electron probe microanalyzer (EPMA) and XRD.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The GGI was calculated to be 0.6 using Eqs. (1) and (2). We confirmed that the GGI agreed well with the chemical element compositions by electron probe microanalyzer (EPMA) and XRD.…”
supporting
confidence: 76%
“…[1][2][3][4][5][6][7] CIGS solar cells have recently shown conversion efficiencies exceeding 22 and 19.8% for small-area cells (0.5 or 1.0 cm 2 ) [8][9][10] and submodules (24 cm 2 ), 11) respectively. However, almost all CIGS solar cells are based on polycrystalline CIGS layers deposited on soda lime glass (SLG) substrates by a three-stage method 12) or by the selenization and sulfurization of metal precursors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, MgF 2 was deposited as an anti-reflection coating by evaporation. 13) For device characterizations, the J-V curves were measured with class AAA solar simulator WXS-350S-L2MS (Wacom) under the standard test condition (STC). The J-V curve was fitted with one-diode model utilizing Lambert-W function to extract the device parameters, 17) which includes the ideality factor (n L ), series resistance (R s ), shunt resistance (R sh ), and reverse saturation current density (J 0 ).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In addition, a low-temperature pulsed electron deposition method for the growth of CIGS films was reported, by which a conversion efficiency of 17.0% for the CIGS solar cell was obtained [10]. Among various deposition methods, the two-step and co-evaporation processes have been widely employed for mass production of the large-scale CIGS-based modules [11,12]. Another favorite approach in CIGS industry is the rapid thermal process (RTP), in which a thin Se layer is first capped on the top of metal precursors, CuInGa compounds, and then the diluted H 2 S gas is supplied to simultaneously sulfurize and selenize the precursors to form the Cu(In,Ga)(S,Se) 2 (CIGSS) films in an RTP furnace [13].…”
Section: Introductionmentioning
confidence: 99%